2005
DOI: 10.1073/pnas.0504248102
|View full text |Cite
|
Sign up to set email alerts
|

Valproate activates bovine leukemia virus gene expression, triggers apoptosis, and induces leukemia/lymphoma regression in vivo

Abstract: Leukemogenic viruses like human T-lymphotropic virus and bovine leukemia virus (BLV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 43 publications
6
74
0
5
Order By: Relevance
“…Therefore, valproate has been selected to evaluate the effectiveness of a gene activation chemotherapy in leukemic sheep. Indeed, valproate effectively activates BLV gene expression in transient transfection experiments and in short-term cultures of primary B-lymphocytes (81). In vivo, valproate administration, in the absence of any other cytotoxic drug, is efficient for the treatment of leukemia/lymphoma in sheep, demonstrating the proof-of-concept of a therapy that targets the expression of viral and/or cellular genes.…”
Section: Modulation Of Viral Expression As Therapymentioning
confidence: 93%
“…Therefore, valproate has been selected to evaluate the effectiveness of a gene activation chemotherapy in leukemic sheep. Indeed, valproate effectively activates BLV gene expression in transient transfection experiments and in short-term cultures of primary B-lymphocytes (81). In vivo, valproate administration, in the absence of any other cytotoxic drug, is efficient for the treatment of leukemia/lymphoma in sheep, demonstrating the proof-of-concept of a therapy that targets the expression of viral and/or cellular genes.…”
Section: Modulation Of Viral Expression As Therapymentioning
confidence: 93%
“…Therapeutic protocols designed to affect HTLV-1-infected cell proliferation or virus replication are still ineffective. 30 A novel approach, called gene-activation therapy, has been proposed, based on preclinical trials in the bovine leukemia virus model 31 and preliminary data on HAM/TSP. 21 The principle is to activate viral gene expression by HDAC inhibitors and thereby expose virus-positive cells to the host immune response.…”
Section: Discussionmentioning
confidence: 99%
“…74 The effectiveness of the valproate therapy as an activator of transcription of the BLV LTR and of p24 synthesis was demonstrated in transient transfection experiments and in short-term cultures of primary B lymphocytes. 75 Indeed, treatment with valproate caused a transient increase of proviral load, a decreased in lymphocyte number, and the induction of tumor regression in leukemic sheep. 75 After valproate treatment, the authors observed a slow and continuous rate of tumor cell destruction, possibly attributed to the induction of an immune response subsequent to the proviral reactivation.…”
Section: Potential Therapeutic Treatment For Blv-infected Cowsmentioning
confidence: 99%
“…75 Indeed, treatment with valproate caused a transient increase of proviral load, a decreased in lymphocyte number, and the induction of tumor regression in leukemic sheep. 75 After valproate treatment, the authors observed a slow and continuous rate of tumor cell destruction, possibly attributed to the induction of an immune response subsequent to the proviral reactivation. In spite of these encouraging results in the leukemic sheep, the animals remained persistently infected.…”
Section: Potential Therapeutic Treatment For Blv-infected Cowsmentioning
confidence: 99%